2009
DOI: 10.1016/j.jasms.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

On-line detection of human skin vapors

Abstract: Vapors released by the skin in the hand of one human subject are detected in real time by sampling them directly from the ambient gas surrounding the hand, ionizing them by secondary electrospray ionization (SESI, via contact with the charged cloud from an electrospray source), and analyzing them in a mass spectrometer with an atmospheric pressure source (API-MS). This gas-phase approach is complementary to alternative on-line surface ionization methods such as DESI and DART. A dominating peak of lactic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…Alternatively, it has been shown that electrospray plumes can efficiently ionize not only analytes from the condensed phase (7,8,10,28,29) but also gaseous compounds (9,18,32), with the latter approach termed "secondary electrospray ionizationmass spectrometry" (SESI-MS) (22,33). These previous studies demonstrate the possibility of real-time detection and identification of VOCs by MS, which can be applied to the characterization of biological samples (19)(20)(21) and could achieve limits of detection as low as parts per trillion (22).…”
mentioning
confidence: 99%
“…Alternatively, it has been shown that electrospray plumes can efficiently ionize not only analytes from the condensed phase (7,8,10,28,29) but also gaseous compounds (9,18,32), with the latter approach termed "secondary electrospray ionizationmass spectrometry" (SESI-MS) (22,33). These previous studies demonstrate the possibility of real-time detection and identification of VOCs by MS, which can be applied to the characterization of biological samples (19)(20)(21) and could achieve limits of detection as low as parts per trillion (22).…”
mentioning
confidence: 99%
“…TMA was specifically added to ESI solutions to mitigate the potential effects of vapor absorption by ESI-generated droplets during the evaporation process. Although the outlet of the copper tube was directed away from the ESI source and when the droplets are micrometers in size, the Stefan flow created by evaporation drives gaseous species away from the droplets (Huckaby and Ray 1989;Martínez-Lozano and de la Mora 2009), it is difficult to guarantee that no vapor uptake occurred. Substantial vapor uptake could influence ion evaporation kinetics, which, in turn, could alter the size and charge distributions of the generated cluster ions (GameroCastano and de la Mora 2000; Gamero-Castaño and Fernández de la Mora 2000; Hogan et al 2008;Hogan and de la Mora 2009).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The new system, which is schematically depicted in Fig. 1, resembles that described in [37], but it uses clean gas to reduce background levels, and a corona instead of the electrospray that allows the temperature of the system to be increased so as to prevent vapor deposition and the subsequent memory effects. The MS (a Qstar XL from Sciex) provides a full spectrum (number of ions detected as a function of their mass to charge ratio) every 0.1 s. The combination of high speed and high sensitivity provided by the new system allowed the analysis of the samples to perform in real time (on-line).…”
Section: Hand Odor Capturementioning
confidence: 99%
“…Therefore, our attributes will be the different mass intervals corresponding to each peak which provides information about a compound of the body odor. Initially, only those mass intervals corresponding to fatty acids were identified based on our previous work [37]; however, these intervals showed to be insufficient to classify people accurately. Peak detection was refined by performing a visual inspection of all the spectrograms, giving as a result 752 common intervals for all the subjects.…”
Section: Pattern Constructionmentioning
confidence: 99%